LE RELAZIONI TRA LE ARENARIE DI SARNICO (CONIACIANO) E LE UNITA' CENOMANIANO-TURONIANE NELL'AREA DI CAPRIOLO - CORNO PENDITA (BS) (BACINO LOMBARDO, ALPI MERIDIONALI) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
The Cenomanian-Coniacian units of the Capriolo - Corno Pendita area belong to the eastern margin of the Lombardy Basin. The Coniacian turbidite sandstone lithosome (Arenarie di Sarnico) unconformably overlies the Cenomanian-Turonian units. The unconformity should be due to slumping and sliding during Late Turonian time. The Arenarie di Sarnico seal the geometries related to the Cenomanian - Turonian synsedimentary tectonic. Evidences for this activity are provided by slumpings and chaotic beds (Early-Late Cenomanian) and by unconformities predating the submarine erosion phase.
Keywords: Cretaceous; Lombardy Basin; Southern Alps; stratigraphy; unconformities.